Performance optimization of CLT (NextGenCLT) - Kurzawinska, Hanna; Tahmasebi, Mohammad (My University, 2023)
Nowadays, the building and construction sector plays a significant role in energy consumption, leading to a growing demand for sustainable solutions and material optimization to reduce CO2 emissions. Cross-laminated timber (CLT) panels have gained attention due to their lightweight and renewable nature, ease of transportation and assembly, and excellent thermal and insulation properties. However, considering the environmental and economic aspects, minimizing the raw material usage in CLT panel production is crucial. To investigate the effects of reducing material in the central part of a CLT panel through the introduction of air gaps in the cross-layers, shear and four-point bending tests were conducted on small and large samples produced in both a university workshop and a CLT factory. The experimental results were compared with FEM models created in MATLAB and ABAQUS. The study focused on conducting shear tests on small specimens with five different configurations of air gaps, analysing their dimensions and arrangement. The deflection and bending capacity were compared with a solid CLT panel, with specific attention given to two configurations featuring central air gaps but differing in size. The shear testing results of CLT panels with various air gap configurations revealed that configuration with overlapping between cross layers demonstrated the highest net rolling shear modulus and net shear strength. The amount of overlap impacted material saving and net shear strength and increasing the air gap size in centrally arranged configurations led to decreasing the net shear strength. From the four-point bending test, the analysis of different configurations reveals that introducing air gaps with dimensions of 6 cm between cross layers leads to a 13% material reduction, which closely follows the bending stiffness of solid specimens. However, increasing the air gap dimension to 12 cm shows a 19% material reduction, but a significant decrease in bending stiffness is observed. The deflection increases with wider air gaps, leading to reduced bending stiffness in configuration with air gaps compared to solid panels. The results emphasize the importance of accurately defining factors such as κs in calculating deflection and bending stiffness, especially for panels with air gaps. Adjusting κs based on the panel's geometry and air gap arrangement is crucial for accurate predictions.
Keywords: Cross-laminated timber, CLT, material optimization, air gaps, shear strength, shear modulus, bending stiffness, strength test